Marketing experiences in the international hospitality industry - Chernyshova, D. V.; Mehovych, S. A.; Pererva, P. G. (My University, 2023)
The report substantiates that the fact that, in our eyes, the development process of value migration gives impetus to the creation of completely new economic and marketing tools for the activities of tourist enterprises on the target international market is important for the enterprises of the international tourism industry: the economy and marketing of impressions is emerging.
Маркетинг вражень в міжнародній індустрії гостинності
Keywords: international tourism; hotel and restaurant business; impression marketing; efficiency